2020
DOI: 10.1071/an18657
|View full text |Cite
|
Sign up to set email alerts
|

Different combinations of sodium monensin and virginiamycin during feedlot finishing of Nellore cattle

Abstract: Context The use of two feed additives, to maximise rumen fermentation, in finishing diets offered to feedlot cattle may positively impact performance. Aims This study, conducted at the São Paulo State University feedlot, Botucatu campus, Brazil, was designed to evaluate the effects of the combined use of monensin (MON; 30 mg/kg of dry matter; (DM)) and virginiamycin (VM; 25 mg/kg of DM) in high-concentrate diets during the adaptation and finishing periods on feedlot performance, carcass traits, feeding behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 41 publications
1
34
0
2
Order By: Relevance
“…Moreover, since the feeding of VM as the sole feed additive increased the DMI without positive impacts on ADG, the cattle fed VM14 had a feed efficiency negatively impacted by 9.4 and 7.5% when compared to the bulls fed MON14 and MONVM14, respectively. It has been previously reported that VM does not negatively impact DMI ( 8 , 11 ) as MON does ( 7 ). As a result, the cattle fed VM14 increased the cost to gain a kilogram of BW by 11.8 and 8.0% in relation to animals receiving MON14 and MONVM14, respectively.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Moreover, since the feeding of VM as the sole feed additive increased the DMI without positive impacts on ADG, the cattle fed VM14 had a feed efficiency negatively impacted by 9.4 and 7.5% when compared to the bulls fed MON14 and MONVM14, respectively. It has been previously reported that VM does not negatively impact DMI ( 8 , 11 ) as MON does ( 7 ). As a result, the cattle fed VM14 increased the cost to gain a kilogram of BW by 11.8 and 8.0% in relation to animals receiving MON14 and MONVM14, respectively.…”
Section: Discussionmentioning
confidence: 79%
“…The cattle fed VM14 showed a greater DMI per meal during feeding behavior evaluations on both adaptation and finishing periods, which explains the greater DMI throughout the study, expressed either in kilograms or as percent of BW, when compared to the cattle fed MON14 or MONVM14 since no differences in meals per day or meal length were detected. It is documented in the literature ( 7 , 8 ) that the negative effect of MON on DMI is related to a lower DMI per meal. As a result, the cattle consuming VM14 increased the DMI fluctuations by 22% (0.90 vs. 0.74 kg; Table 2 ) throughout the study in relation to the cattle fed MON14; however, the average daily fluctuation, expressed in percent, was 6.78 and 5.35% for the cattle fed VM14 and MON14, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sodium monensin, the most popular feed additive among feedlot consulting nutritionists (Table 10), is an ionophore, which has been cited in all past Brazilian (Millen et al, 2009;Oliveira and Millen, 2014;Pinto and Millen, 2019) and American surveys (Samuelson et al, 2016) as the primary type of feed additive used in finishing diets. Virginiamycin has been cited as the secondary feed additive used by their clients in finishing diets, since the combination of monensin and virginiamycin in finishing diets has become popular in the past four years based on promising results related to increasing carcass weight (Rigueiro et al, 2020). However, we cannot guarantee, based on the results of this survey, that all nutritionists' clients that use virginiamycin as secondary feed additive also use sodium monensin as their primary feed additive.…”
Section: Recommended Nutrient Composition For Finishing Dietsmentioning
confidence: 81%